The experiences of emergency department use by street-involved youth: Perspectives of health care and community service providers. (8th August 2016) - Nicholas, David B.; Newton, Amanda S.; Kilmer, Christopher; Calhoun, Avery; deJong-Berg, Margaret A.; Dong, Kathryn; Hamilton, Faye; McLaughlin, Anne Marie; Shankar, Janki; Smyth, Peter
ABSTRACT: Street-involved (SI) youth represent a significant proportion of urban homeless populations. While previous research has identified SI youth as substantial users of emergency department (ED) services and has examined their experiences of ED care, little is known about the experiences and perceptions of the service providers who assist these youth with health care related issues. Using grounded theory, individual interviews and focus groups were conducted with 20 community agency staff serving SI youth, 17 health service providers, two hospital administrators, and two hospital security personnel regarding their experiences in providing or facilitating ED care for SI youth. Results identify differences in expectations between SI youth and hospital staff, along with service issues and gaps, including relational barriers and resource constraints. Implications for practice and policy development are offered.